A new snake of the genus Atractus Wagler, 1828 (Reptilia: Squamata: Colubridae) from Kaieteur National Park, Guyana, northeastern South America - Kok, Philippe J.r. (Zootaxa, 2006)
A new colubrid snake of the genus Atractus Wagler 1828 is described from Kaieteur National Park, west-central Guyana. The new species differs from all other congeners by the combination of two postoculars, 15 dorsal scale rows, eight supralabials, seven to eight infralabials, loreal much longer than high, six maxillary teeth, and a color pattern consisting of irregular red or pale red markings, sometimes forming an incomplete broken dorsolateral stripe, on a medium brown to brownish black ground color, and heavy brownish black mottling on a yellowish cream venter. A key to the species of the genus Atractus from Guyana is provided.